Analisis Pendapatan Usahatani Jagung Manis (Zea mays L. Saccharata) Di Perkebunan Wawo Kota Tomohon - Wowiling, Marisni Nofia; Memah, Melsje Yellie; Talumingan, Celcius (Sam Ratulangi University, 2023)
The purpose of this study was to analyze the income of sweet corn farming in Wawo Plantation, Tomohon City. The research was conducted for 3 months starting from March to May 2023. The research was conducted in Wawo Plantation, Tomohon City, North Sulawesi Province. The data used were collected from primary data through surveys and direct interviews with farmers and using questionnaires, and secondary data obtained from previously documented data, both in the form of data from the Tomohon City BPP office and sources obtained from the internet. Sampling using simple random sampling method, which was taken from Sweet Corn farmers in Wawo Plantation Tomohon City as many as 51 farmers. The research data were analyzed using descriptive quantitative analysis method to determine the total cost, revenue and income. The income of sweet corn farming in Wawo Plantation, Tomohon City was Rp13,107,131 per farmer per growing season and Rp7,461,444 per hectare per growing season where this amount was obtained from the total revenue of Rp18,900,000 per farmer per growing season and Rp10,444,000 per hectare per growing season minus the total cost of Rp5,792,869 per farmer per growing season and Rp2,982,556 per hectare per growing season from this amount of income shows sweet corn farming is profitable.